A patient with abdominal pain and obstructive jaundice - Dindar, Gökhan; Sezikli, Mesut; Çam, İsa; Turgut, Hamdi Taner (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Dindar G, Sezikli M, Çam İ, Turgut HT. A patient with abdominal pain and obstructive jaundice. Turk J Gastroenterol 2018; 29: 233-6.